KARAKTERISTIK PAPAN SEMEN BERBAHAN BAKU KAYU KEMIRI (Aleurites moluccana) YANG DIBUAT MELALUI INJEKSI KARBON DIOKSIDA (CO2) UNTUK PERCEPATAN CURING SEMEN - Su hasman; Herpina Yanti; Ba kri (Tengkawang : Jurnal Ilmu Kehutanan, 2012)
The main problem of cement board manufacturing technology is the length of curing time required to achieve the complete hardening cement. In this reseach, acceleration curing technology has been developed through injection of carbon dioxide (CO2). This research was aimed to analyze the characteristics of cement boards that are made by using CO2 to accelerate the curing process. The wood materials used in this study was candlenut (Aleurites moluccana). Cement board is made with the composition of wood, cement, water: 1: 2.5: 1.25 with a target density of 1 g cm-3. CO2 injection is applied in three phase namely, liquid phase (15oC temperature & 50 kg cm-2 pressure), gas phase (27 oC temperature & 50 kg cm-2 pressure), and super-critical phase (35 oC temperature & 80 kg cm-2 pressure). Each phase is combined with three levels treatment time, namely, 10, 30, and 60 minutes. As a control, cement board with a conventional curing process that was conditioned for 28 days in room condition has been produced. The research results indicated that CO2 injection applications in various phases to produce cement board have better characteristics compared to that of conventional cement board. Cement board using CO2 injection in liquid phase has better characteristics compared to those of gas and super critical phases. However the optimum conditions achieved in the injection time for 60 minutes, while applications with supercritical CO2 has been able to achieve the best results with 10 minutes of injection time. Key words. Cement board, CO2, curing, candlenut wood